Poverty, Inequality, and the Local Natural Resource Curse - Loayza, Norman (World Bank, Washington, DC, 2013)
The extent to which local communities benefit from commodity booms has been subject to wide but inconclusive investigations. This paper draws from a new district-level database to investigate the local impact on socioeconomic outcomes of mining activity in Peru, which grew almost twentyfold in the last two decades. The authors find evidence that producing districts have better average living standards than otherwise similar districts: larger household consumption, lower poverty rate, and higher literacy. However, the positive impacts from mining decrease significantly with administrative and geographic distance from the mine, while district-level consumption inequality increases in all districts belonging to a producing province. The inequalizing impact of mining activity, both across and within districts, may explain part of the current social discontent with mining activities in the country, even despite its enormous revenues.